Exosomes, Stem Cells and MicroRNA Aging, Cancer and Age Related Disorders (Advances in Experimental Medicine and Biology,, 2018)
This volume provides insight into the pivotal roles of stem cells, exosomes and other microvesicles in biofunction and molecular mechanisms and their therapeutic potential in translational nanomedicine. It further highlights evidence from recent studies as to how stem cell derived exosomes and microRNAs may restore and maintain tissue homeostasis, enable cells to recover critical cellular functions and begin repair regeneration. These early studies in animal models of aging also show evidence of improved immune, cardiovascular and cognitive functions as well as improved health span and life span. The use of exosomes from body fluids to define specific biomarkers for various tumors may also clear the path to patient-targeted treatments by developing exosome-derived microRNA based cancer therapeutics. It is essential reading for graduate students, research fellow and biomedical researchers in academia or the pharmaceutical or biotech industries.